PSYCHOLOGICAL FEATURES OF OFFICIALS OF INTERNAL AFFAIRS IN LEARNING FOREIGN LANGUAGES - Boybutayev Jaxongir Egamberdi o`g`li (Galaxy International Interdisciplinary Research Journal, 2022)
This article indicates how significant psychological characters of Officials of Internal Affairs in acquiring foreign languages. In particular, psychological features are significantly productive to learn a great number of foreign languages for some of Officials of Internal Affairs. Additionally, the author attempts to show some new experiences as well as new strategies in a braod way.